2014
DOI: 10.1155/2014/509027
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of Ecto-Nucleotidases CD39 and CD73 in Human Endometrial Tumors

Abstract: One of the strategies used by tumors to evade immunosurveillance is the accumulation of extracellular adenosine, which has immunosupressive and tumor promoting effects. The study of the mechanisms leading to adenosine formation at the tumor interstitium are therefore of great interest in oncology. The dominant pathway generating extracellular adenosine in tumors is the dephosphorylation of ATP by ecto-nucleotidases. Two of these enzymes acting sequentially, CD39 and CD73, efficiently hydrolyze extracellular AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 31 publications
(38 reference statements)
1
44
0
Order By: Relevance
“…This phenomenon suggests that, in some cases, tumor-associated stromal cells may potently hydrolyze ATP and, in concert with CD73, generate adenosine, thereby producing an "immunosuppressive environment" that favors tumor growth. This expression of CD39 by tumor-associated stromal cells has been detected previously in ovarian (33) and endometrial tumors (31) and requires further investigation.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This phenomenon suggests that, in some cases, tumor-associated stromal cells may potently hydrolyze ATP and, in concert with CD73, generate adenosine, thereby producing an "immunosuppressive environment" that favors tumor growth. This expression of CD39 by tumor-associated stromal cells has been detected previously in ovarian (33) and endometrial tumors (31) and requires further investigation.…”
Section: Discussionsupporting
confidence: 60%
“…CD39 promotes melanoma and colon cancer growth and metastasis in mice (12,13,30), and CD39 disruption or blockade facilitates NK cell-mediated tumor eradication in vivo (13). CD39 is also expressed by other cell types in the tumor environment, such as stromal cells (31) and endothelial cells (32), and may stimulate tumor progression. Furthermore, results from a recent study suggested that, similar to CD73, CD39 might be expressed by some tumor cells (33).…”
Section: Introductionmentioning
confidence: 99%
“…This expression pattern reflects the advantage that these enzymes confer to cancer cells by the degradative conversion of extracellular ATP, which promotes immunosurveillance, into adenosine, which exerts potent immunosuppressive effects. [191][192][193][194][195][196][197] Of note, autophagy is also important for the perception of cell death as immunogenic because it contributes to several aspects of cellular immune responses, including the differentiation, survival and activation of myeloid and lymphoid cells. [198][199][200] The release of HMGB1 from cells succumbing to ICD requires the permeabilization of both the nuclear and plasma membranes, de facto constituting a post-mortem event.…”
Section: Immunogenic Cell Death Signalingmentioning
confidence: 99%
“…CD73 expression is also associated with poor prognosis in several types of tumors (31), including colorectal cancer (32), gastric cancer (33), gallbladder cancer (34), serous ovarian cancer (35), triple negative breast cancer (36), and malignant melanoma (37). In endometrial tumors, no differences in the CD73 expression among tumors were observed with enzyme assays in either tissue slices or tissue homogenates (38). To the best of our knowledge, there has been no report on CD73 expression in GI-NENs.…”
Section: Who 2010 Classification ------------------------------------mentioning
confidence: 99%